2020
DOI: 10.1111/dar.13117
|View full text |Cite
|
Sign up to set email alerts
|

Self‐managing illicit stimulant use: A qualitative study with patients receiving injectable opioid agonist treatment

Abstract: Introduction and Aims. Illicit stimulant use is prevalent among patients receiving injectable opioid agonist treatment (iOAT) and has been associated with early treatment discontinuation and illicit opioid use. Despite these concerns, little is known about the use of illicit stimulants in this population. As such, this study aimed to explore the processes by which patients receiving iOAT engage in the use of illicit stimulants. Design and Methods. One-on-one in-depth qualitative interviews were conducted. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Fourth, while many clinical trials have investigated the effectiveness of this medication separately among people with cocaine or methamphetamine use disorder, participants in the present study reported cocaine and/or methamphetamine use. Nevertheless, a prior qualitative study investigating patients’ illicit stimulant use in this study setting (iOAT clinic) found no differences across themes by reported illicit stimulant use type [ 17 ]. Furthermore, the present study includes only participants who remained engaged with the iOAT clinic and thus the perspective of people who received dextroamphetamine but were not well engaged in iOAT are not represented.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Fourth, while many clinical trials have investigated the effectiveness of this medication separately among people with cocaine or methamphetamine use disorder, participants in the present study reported cocaine and/or methamphetamine use. Nevertheless, a prior qualitative study investigating patients’ illicit stimulant use in this study setting (iOAT clinic) found no differences across themes by reported illicit stimulant use type [ 17 ]. Furthermore, the present study includes only participants who remained engaged with the iOAT clinic and thus the perspective of people who received dextroamphetamine but were not well engaged in iOAT are not represented.…”
Section: Discussionmentioning
confidence: 96%
“…Analysis began with an inductive, data-driven approach, whereby codes were attached to the data to directly reflect participants’ words, rather than applying a pre-existing coding framework. Coding was conducted by author HP who has extensive experience collecting and analyzing qualitative research data with patients in the iOAT setting [ 17 – 19 ]. Data collection began with broad questioning about the benefits and challenges of the medication, and subsequent data collection included more specific and focused questioning on sub-topics identified as important in initial data collection.…”
Section: Methodsmentioning
confidence: 99%
“…To date, preliminary research has found that when adequately dosed, the provision of stimulants alongside MOUD reduces both illicit opioid and stimulant use. [54][55][56][57] Given the potential benefits of prescribing both prescription opioids and stimulants to AYA, future research investigating the use of both types of medications and their impact on the health of AYA may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis began with an inductive, data-driven approach, whereby codes were attached to the data to directly re ect participants' words, rather than applying a pre-existing coding framework. Coding was conducted by author HP who has extensive experience collecting and analyzing qualitative research data with patients in the iOAT setting [17][18][19]. Data collection and analysis were iterative, where initial codes generated from analysis of the focus group data offered insights into important areas of further inquiry for subsequent interviews.…”
Section: Discussionmentioning
confidence: 99%